Comparative Law in Asia: the case for intra-Asia intensification - Shuaib, Farid Sufian (Faculty of Law, Universitas Muhammadiyah Yogyakarta in collaboration with the Indonesian Association of Comparative Laws, 2018)
It is important to consider the subject of comparative law with what is happening around the world stage. One inference that we could make from Brexit (namely the success of the referendum for United Kingdom to leave the European Union) and the support received by the far right populist political parties in Europe, (such as the National Front in France) is that nationalism is on the rise. Of course, nationalism helps the creation of states in the first place and thus is not necessarily a terrible thing. Moreover, nationalism could be used to harness unity and cohesiveness in a nation in order to be a developed country, so that the agenda for development could be executed and achieved. However, the language of nationalism that one could hear from some parts of the world is about superiority and exclusion. This paper seeks to consider the state of comparative law in Asia and its importance.